An engineering feasible metastructure: Ring-spring-resonator based sandwich metabeam for vibration attenuation. (15th December 2022) - Shi, Dongyu; Liu, Yang; Chen, Hailong; Meng, Fanmao; An, Xiyue; Jin, Fengnian; Fan, Hualin
Highlights: Ring-spring-resonator based sandwich metabeam was designed, made and tested. Ring-spring-resonator based sandwich metabeam has better vibration attenuation. Multi-frequency resonators greatly widen bandgap of vibration attenuation. Ring-spring-resonator based sandwich metabeam is engineering feasible. Abstract: Local resonance mechanisms have attracted a great deal of attention due to their bandgap property. In this paper, an engineering feasible ring-spring-resonator based metabeam (RSR-B), consisting of wire rope isolators and mass blocks, was designed based on the mechanism of two-stage vibration system and local resonance. Three kinds of metabeams were prepared and their vibration attenuation properties were investigated theoretically, numerically and experimentally. These metabeams are easily made and have many advantages in vibration attenuation over ordinary vibration isolation beams. The first and second metabeams are both merely manufactured by one kind of ring-spring-mass resonators, which means the monotonic and narrow bandgap. Considering the arrangement form of resonators, two kinds of resonators are combined to form the third metabeam, which has an obviously widened bandgap, completely covering the bandgaps of the first and the second metabeams.